PEMANFAATAN MEDIA PEMBELAJARAN E-LEARNING - Endar Sulistyowati; Riska Bayu Aditya (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
The Indonesian government has begun to issue policies for implementing the new normal in various sectors, including the education sector. This of course makes the public must be able to condition the situation with the new rules made by the government. The rapid development of the world of education cannot be separated from the use of increasingly sophisticated technology. Global demands always demand the world of education to be in line with the development of information and communication technology for the world of education, especially in the learning process. For this reason, this study aims to (1) provide alternative learning media for lecturers and students using e-learning, (2) find out the benefits of educational technology with e-learning as a learning medium in the new normal era. Keyword : e-learning media, google classroom